KREATIVITAS GURU PAI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Nurkhalijah Nurkhalijah; Khairuddin Khairuddin (PAI RAFAH, 2023)
This study aims to determine the creativity of pai teachers in increasing student learning motivation at SMP Negeri 1 Raya Kahean Kab. Simalungun. In this descriptive qualitative research, data were collected through observation, interviews, and documentation. The results of this study indicate that the form of PAI teacher creativity in increasing student learning motivation at SMP Negeri 1 SMP Negeri 1 Raya Kahean Kab. Simalungun can be seen starting from designing, planning learning, and implementing learning. Teacher creativity in planning learning can be seen when teachers can motivate students to be religious, such as dhuha prayer and dzuhur prayer in congregation, before and after learning activities begin the teacher always gives advice to students to always carry out Allah's commands and leave his prohibitions such as dhuha prayer in congregation, dzuhur prayer in congregation in the mushalla, and maintain good morals as a Muslim. While the obstacles students face in increasing learning motivation at State Junior High School 1 Raya Kahean Kab. Simalungun The obstacles experienced by students towards increasing learning motivation are the lack of learning innovations delivered by teachers, inadequate places of worship, and the influence of the surrounding environment. then the task for public school pai teachers 1 Raya Kahean is to increase self-creativity and also develop innovations in learning, as well as for schools to emphasize their students to apply religious foundations, both in terms of cleanliness and association so that students feel comfortable and calm in learning.